Diversity in returns to education in Europe. The empirical importance of the systems of the regression approach - Pipień, Mateusz; Roszkowska, Sylwia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The aim of the paper is the formal comparison of returns to education for a set of European countries. We apply the system of Seemingly Unrelated Regression Equations (SURE) to obtain the parameters of the Mincerian equations. The differences between the parameters were tested given two alternative stochastic assumptions. In the first model, no contemporaneous correlations between error terms in the system are imposed. In the second approach, the unrestricted covariance matrix is considered, making error terms stochastically dependent. The contemporaneous correlations of error terms in the SURE system were empirically supported. The rich parameterisation of the covariance matrix of contemporaneous relations reduced statistical uncertainty about differences in parameters describing return to education. Therefore, the country heterogeneity of return on education, which seems intuitively correct, was obtained in the system of regressions with a complex stochastic structure
Argumenta Oeconomica, 2018, Nr 2 (41), s. 61-90
Keywords: Mincer equation; returns to education; SURE; Zellner estimator